Pengembangan Aplikasi Klasifikasi Sepatu Air-Jordan Berbasis Web - Adipratama, Virya (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2024)
This research is motivated by the number of series and the similarities of Air Jordan sneakers so that the series of the Air Jordan sneakers is hard to recognize. Therefore, this research intends to solve the Air Jordan sneakers classification problem with building a web-based application to classify Air Jordan sneakers images. This research aims to develop a web-based software to classify Air Jordan sneakers images. The data that are used in this research are 11641 Air Jordan sneakers images for training and 560 Air Jordan sneakers images for testing with 35 classes. The methods that are used in this research is incremental methods which is made with two increments. The first increment produces a classification model and the second increment produces an application that implemented the classification model. The result of this research is a web-based application that can classify an Air Jordan sneakers image with the output of the predicted series of that Air Jordan sneakers image.